PERAN PENATA ARTISTIK DALAM FILM FIKSI DARA DALAM BELENGGU INSTITUT SENI INDONESIA BALI - Arinanda Kesuma; Ni Kadek Dwiyani; Desak Putu Yogi Antari Tirta Yasa (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2026)
The internship program is part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, which aims to connect academic learning with professional industry practice. The author completed an internship at PT. Boklaa Bali Film, a company engaged in film production and creative media content. The internship focused on the role of the art department in the production of the fictional short film Dara Dalam Belenggu. The internship activities were carried out through observation, interviews, active participation, and direct documentation during the pre-production, production, and post-production stages. Through this process, the author gained knowledge regarding the workflow and responsibilities of the art department, as well as strategies for addressing visual and technical challenges in the field. These challenges included adapting set designs to the narrative concept, selecting appropriate props, and managing color schemes and visual textures to support the emotional atmosphere of each scene. The application of semiotic elements also contributed to strengthening the storytelling and visual meaning of the film. In addition, the internship provided skill development in creating set design sketches, arranging spatial layouts, and collaborating with other departments such as cinematography, lighting, and costume. From a technological perspective, the author learned to use design and visualization software, including SketchUp and Coohom, to support artistic planning and set design development in accordance with the film’s narrative needs. The internship process was analyzed using a descriptive approach to examine the relationship between theoretical knowledge obtained in academic studies and its application in professional practice. The results of this internship enhanced the author’s technical competencies in production design and increased awareness of the importance of interdepartmental collaboration in film production, contributing to better preparation for entering the creative industry.